Freeze-Thaw Stress: Effects of Temperature on Hydraulic Conductivity and Ultrasonic Activity in Ten Woody Angiosperms. Issue 2 (16th December 2013) - Charrier, Guillaume; Charra-Vaskou, Katline; Kasuga, Jun; Cochard, Hervé; Mayr, Stefan; Améglio, Thierry
Abstract : Gas segregation and air seeding are both involved in embolism development in angiosperms . Abstract: Freeze-thaw events can affect plant hydraulics by inducing embolism. This study analyzed the effect of temperature during the freezing process on hydraulic conductivity and ultrasonic emissions (UE ). Stems of 10 angiosperms were dehydrated to a water potential at 12% percentage loss of hydraulic conductivity (PLC ) and exposed to freeze-thaw cycles. The minimal temperature of the frost cycle correlated positively with induced PLC, whereby species with wider conduits (hydraulic diameter) showed higher freeze-thaw-induced PLC . Ultrasonic activity started with the onset of freezing and increased with decreasing subzero temperatures, whereas no UE were recorded during thawing. The temperature at which 50% of UE were reached varied between −9.1°C and −31.0°C across species. These findings indicate that temperatures during freezing are of relevance for bubble formation and air seeding. We suggest that species-specific cavitation thresholds are reached during freezing due to the temperature-dependent decrease of water potential in the ice, while bubble expansion and the resulting PLC occur during thawing. UE analysis can be used to monitor the cavitation process and estimate freeze-thaw-induced PLC .